Experimental Measurement of Vacuum Evaporation of Aluminum in Ti-Al, V-Al, Ti6Al4V Alloys by Electron Beam - Dawei Wang (MDPI AG, 2021)
Titanium alloys have been widely used in aerospace engineering due to their excellent mechanical properties, especially their strength-to-weight ratio. In addition, Ti6Al4V (TC4) alloy is the most widely used among α+β alloys. The main three elements of TC4 alloy are titanium (Ti), aluminum (Al) and vanadium (V). Since the boiling point of aluminum is much lower than the melting point of the other two elements, the consistency of TC4 alloy during smelting, additive manufacturing and surface treatment is difficult to control. Therefore, in order to study the difficult problem of composition control in TC4 alloy production, we measured the vacuum evaporation of Al, Ti and V in Ti-Al, V-Al and TC4 alloys, and tracked the changes of molten pool temperature, heating time and weight. According to the results, the Al started to evaporate near 1300 ± 10 °C in vacuum and totally evaporated after 225 s heating to 1484 °C at 10−2 Pa. However, V and Ti barely evaporated below 2000 °C. The Al in Ti-Al alloy started to evaporate at 1753 ± 10 °C and lost 20.6 wt.% aluminum during 500 s at 1750~1957 °C. The Al in V-Al alloy started to evaporate at 1913 ± 10 °C and lost 26.4 wt.% aluminum during 543s at 1893~2050 °C. The Al in TC4 alloy started to evaporate at 1879 ± 10 °C and lost 79.6 wt. % aluminum after 113 s at 1879~1989 °C. The results indicate that smelting TC4 alloy with Ti-Al and V-Al alloys by EBM below 1900 °C improves the consistency and performance. Additionally, the lowest loss of Al occurred in the additive manufacturing of TC4 alloy below 1900 °C.